Roman and late-Roman glass from north-eastern Italy: The isotopic perspective to provenance its raw materials. (October 2015) - Gallo, Filomena; Silvestri, Alberta; Degryse, Patrick; Ganio, Monica; Longinelli, Antonio; Molin, Gianmario
Abstract: In this study, the strontium, neodymium and oxygen isotopic composition of Roman (1st–3rd century AD) and late-Roman glass (4th–6th century AD) from Adria and Aquileia, two of the most important archaeological sites of north-eastern Italy, is discussed. The majority of glass analysed, independent from age, shows values of strontium isotope ratios close to that of modern seawater, indicating that the source of lime in the glass was marine shell, and likely coastal sands were used in its production. The Nd signature of all late-Roman glasses from Aquileia and of the majority of the Roman ones from Adria, independent from their chemical composition, is homogeneous and higher than −6 εNd, supporting the hypothesis of an eastern Mediterranean origin, probably located on Syro-Palestinian coast. However, the composition of late-Roman samples with HIMT signature, with lower 87 Sr/ 86 Sr values correlated to higher contents in Fe2 O3, TiO2, MgO and lower contents in CaO, suggests an area of origin for this glass on the Egyptian coast. In addition, the different Nd signatures of two Adria Roman glasses (εNd < −7) suggest their primary production in western Mediterranean. Oxygen isotopes proved to be a further diagnostic method to discriminate natron and soda plant ash glass, and different silica sources, in the case of the soda plant ash glass. The combination of isotopic and chemical data supports the hypothesis of an eastern Mediterranean origin for late-Roman glass, which may be produced in few primary workshops on the Syro-Palestinian and Egyptian coast, although not necessarily in the same ateliers as have been identified so far. In the case of the Roman glass investigated, although the majority of data suggests an eastern Mediterranean origin, on the basis of Nd isotopes and chemical compositions, the existence of other primary glass producers located in the western Mediterranean can be suggested. Highlights: Sr, Nd and O isotopic data of Roman and late-Roman glass from Adria and Aquileia. Sr isotopes suggest that coastal sands were used for Roman and late-Roman glass. Nd signatures support the hypothesis of an eastern Mediterranean origin. Primary production in western Mediterranean is also suggested for Roman glass. Oxygen isotopes discriminate different silica sources in soda ash glass.